The Humanistic Economics of Krausismo - Claus Dierksmeier (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
Current efforts of reconciling economics with ethics, as exemplified by the works of Amartya Sen, may be assisted by a glance back into the history of ideas. A tradition typically overlooked in Anglo-American scholarship, the Spanish and Latin America movement of krausismo, proposed a conception of a humanistic economics already in the late 19th century. This article reconstructs the intellectual premises of said tradition, portrays its participatory agenda for an integration of ethical norms into economic policy in a selected case and concludes with reflections on how to advance an economics in tune with society's normative aspirations.
Keywords: B31; B41; Z10; Z13; Z18; B10; B13; B19; 330; Amartya Sen; Economic Ethics; Economic Philosophy; Freedom; Deliberative Democracy; Krause; Krausismo